Species complex or complex species? Integrative taxonomy of the land snail genus Rossmaessleria (Gastropoda, Helicidae) from Morocco and Gibraltar. Issue 4 (3rd July 2016) - Walther, Frank; Neiber, Marco T.; Hausdorf, Bernhard
Abstract : We applied an integrative approach to re-evaluate the taxonomy of the conchologically highly diverse land snail genus Rossmaessleria from the Rif Mountains in Morocco and from Gibraltar, which has been classified into 12 nominal species so far. An analysis of cox1 and 16S rDNA sequences using the General Mixed Yule-coalescent approach with a single or multiple thresholds, its Bayesian implementation as well as the Automatic Barcode Gap Discovery method indicated that all Rossmaessleria populations can be classified into a single species, R. scherzeri (Zelebor, 1867). This result is confirmed by the lack of diagnostic differences in the genitalia as shown in a principal component analysis of the genital measurements. The variation of shell characters also does not allow an unambiguous subdivision of the complex. However, the populations of a mountain or a mountain ridge share characteristic combinations of shell characters so that they can be classified as geographic subspecies. The delimitation of the subspecies and their distribution is discussed and three subspecies are described as new to science: R . scherzeri periclitata ssp. nov. R . scherzeri ingae ssp. nov., and R . scherzeri eleanorae ssp. nov. http://zoobank.org/urn:lsid:zoobank.org:pub:187FE235-A257-423F-8FC3-957117546400